Can You Rewrite As A FUNCTION OF X Using Function Notation For 2x + 3y=4?

2 Answers

Oddman Profile
Oddman answered
First, you solve for y in terms of x.
2x + 3y = 4
3y = 4 - 2x
y = 4/3 - (2/3)x

Now, replace "y" with "F(x)"
F(x) = 4/3 - (2/3)x

Oddman Profile
Oddman answered
An equation such as y = x+3 can be rewritten showing y as a function of x:
Y(x) = x+3

Sometimes, the function is given a different name.
F(x) = x+3

Conventionally, function names are single letters in the sequence F, G, H. Of course, the function name can be anything you like, and is not restricted to a single letter.

Answer Question

Anonymous